Severe Presentation of Cannabinoid Hyperemesis Syndrome With Mixed Acid–Base Disorder and Cardiac Complications: A Case Report - Giovanni Mantelli; Armando Fiore; Caterina Barberi; Barbara Zaia; Giorgio Ricci; Massimo Carollo; Fabio Malalan (Case Reports in Medicine)
Conclusion: This case underscores the importance of recognizing CHS as a potential etiology in patients with recurrent vomiting and a history of chronic cannabis use, even in the presence of atypical findings such as profound electrolyte imbalances and cardiac abnormalities. Given the protracted recovery period associated with CHS, early identification and patient education regarding cannabis cessation are crucial in preventing recurrent episodes.